Analisis Efisiensi Produksi Usaha Ternak Ayam Ras Pedaging (Broiler) pada Pola Kemitraan Contract Farming Di Kabupaten Kampar - Elsyintia Dwi Putri; Cepriadi Cepriadi; Fajar Restuhadi (Politeknik Pertanian Negeri Payakumbuh, 2020)
Chicken broiler is the main commodities and largest in Indonesia, where Kampar district into production centre in the province of Riau. According to the companys partners, breeder who partnered with the pattern contract farming hasn't been able to combine the use of livestock production facilities as well as labor. This resulted in not maximizing the profits obtained by breeders. The purpose of the research was to analyze broiler chicken farming and analyze the efficiency of broiler chicken production. Analytical method used is the analysis method of broiler chicken flocks and the DEA method. Respondents needed is 40 farmers who have partnered with the contract farming pattern. The results showed that the production costs of Rp.180.031.229 /period, revenue Rp.203.573.865/period, so that the profit amounting to Rp 23.542.636/period with R/C ratio of 1.13. The results of the efficiency analysis show that inefficient farmers are more numerous than those who have been efficient. It showed breeders hasn't been able to use the minimum input produce output that is optimal and maximum profit.